Quand les « Diables » deviennent de bien jeunes maires - Irène Dos Santos (Ateliers d'Anthropologie)
Through a study of the Boys’ Festival, an initiation and regeneration rite performed in the middle of winter, this article aims to examine the place allocated to young people, and the place they claim for themselves in a changing Portuguese society. The Boys’ Festival is an arena that showcases the tensions that surround the redefinition of “tradition”, in the sense of norms relating to gender relations and a vision of society, of which young people are the driving force. The antagonisms that come to the surface during the various ritual sequences reveal the tension between young people’s desire to impose their authority—to show that they are capable of being responsible and perpetuating the tradition—and elders’ deprecation of their ritual authority, and consequently of their claim to exist. The absence of girls, potential fiancées, shows the rejection of male domination and indicates the possible end of the ritual’s raison d’être.